ABCs or 123s? The independent contributions of literacy and numeracy skills on health task performance among older adults. Issue 8 (August 2015) - Smith, Samuel G.; Curtis, Laura M.; O'Conor, Rachel; Federman, Alex D.; Wolf, Michael S.
Highlights Literacy and numeracy are highly correlated. In multivariable analysis, literacy and numeracy were independent predictors of health task performance. Literacy and numeracy are complementary skills and both are important for health self-management.